(untitled) (Fiep Bulletin - online, 2014)
The function of the school is intended to help the integral development of the students stimulating critical sense and the autonomy, in search of training for people with significant expertise in society, enabling a tangible contribution to inclusive education. This research proposes a review of the training of teachers of Physical Education belonging to the third and the fourth rounds of the fundamental teaching of Guarapuava-Pr, in school environments for inclusion. The methodology will be ethnographic approach, using the case of interviews semiestruturadas in relation to the training and examination of the acts teaching, seeking articulate the special education and regular education to encourage inclusive education. The training will be examined through academic perspective (courses in graduate and post-graduate) and permanent (experiences and training courses) for performance in a school environment inclusive. Meanwhile, reflect on the training of teachers, examining ways to work if the answers are positive and / or negative to the process of inclusion. The findings may assign some ideas hypothetical apart. The first is a qualification that allows the teacher to become multifunctional and develop through the inclusion of adjustments the needs of all students or in a second case, cover in the same environment specific work for regular class and one for special class, providing segregation for students with special educational needs. Therefore, through this proposal the search is sustained on the importance of analyzing the quality of a significant share of education in society, seeking reflect that the training of teachers intensify the conditions of the students to develop through the difficulties. Thus, it may provide subsidies to identify whether the work of teachers of Physical Education through its training contributes to effective education.